Proteína Klotho, biomarcadores de lesão endotelial e déficit cognitivo em pacientes com doença renal crônica não dialítica - Queiroz, Anaiara Lucena (2023)
Chronic Kidney Disease (CKD) is characterized by progressive kidney damage evidenced by a reduction in the glomerular filtration rate. Cognitive dysfunction is common in patients with CKD and the exact pathophysiology of cognitive impairment in CKD is not completely understood. Serum levels of Klotho protein are significantly lower in patients with CKD than in healthy patients, also reducing cerebral Klotho levels. The Klotho protein, produced by the kidney, coreceptor of FGF23, appears to be necessary for neuroprotection. To understand the correlation of the Klotho protein with cognitive disorders, 52 patients were selected, 40 with non-dialytic CKD followed at the Nephrology outpatient clinic of the Walter Cantídio University Hospital (HUWC), Federal University of Ceará (UFC), and 12 patients from the group control. Cognitive function was assessed through the application of the following neuropsychological tests: Rey's Auditory-Verbal Learning Test (RAVLT), Five Digit Test (FDT), Foward and backward digit span, Corsi's Cube Task, Stroop Test, Trial Making Test (TMT) and Phonemic and Semantic verbal fluency tasks. Serum levels of Klotho, FGF23 and endothelial injury biomarkers (VCAM-1, Angiopoietin 1 and 2) were measured. Klotho serum levels were significantly decreased in patients with CKD when compared to the control group (p=0,015). VCAM-1 and Angiopoietin 2 were significantly increased in patients with CKD compared to the control group (p=0,012 and p=0,03, respectively). Increased FGF23 levels were associated with reduced glomerular filtration rate (rho=-0,636, p=0,035) and lower scores on a RAVLT memory test (rho= -0.626, p=0,04) in patients with moderate/severe CKD. It was strongly evidenced that the reduction of Klotho protein serum levels in patients with moderate/severe CKD (GFR < 45 mL/min/ 1,73m2) are associated with elevated levels of VCAM 1 (p=0,019) and both, the reduction of serum Klotho levels and increased VCAM-1 were associated with worse outcome in several domains of cognition on neurocognitive tests. These data correlate serum Klotho protein with cognitive impairment and suggest that serum Klotho levels are a marker of incipient cognitive impairment, even in patients without a clinical diagnosis of cerebrovascular disease.